Consular Jurisdiction : On the History of the Judicial Functions of Consulates (12th-20th Century) - Regula, Lars; Ulbert, Jörg (Early Modern History and Modern History E-Books online, Collection 2026., 2026)
For today's practitioners, the history of the judicial functions of consulates is far more colourful and obscure than modern consular law might suggest. Take, for instance, Consul Annibale de Rossetti in Egypt, who had to arbitrate a lawsuit between two German merchants and was completely overwhelmed. De Rossetti neither knew German nor was he familiar with the law he was expected to apply. Modern consuls often react with disbelief at the fact that their predecessors acted not only as judges, but also as regulatory authorities and bailiffs. This volume brings together contributions on the history of the legal roles and functions of consulates, spanning from America to China and from their origins in the Middle Ages to the modern consulate. Contributors are: Marcella Aglietti, Eleonora Angella, Arnaud Bartolomei, Thibault Bechini, Giorgio Ennas, Ana Belem Fernández Castro, Juliette Françoise, Laura Galoppini, Sacha Gauthier Olssy, Thomas Gidney, Berna Kamay-Ulusay, Jessica Marglin, Cédric Quertier, Lars Regula, Victor Simon, Jörg Ulbert, and Dominique Valérian. L'histoire des fonctions judiciaires des consulats est bien plus riche et obscure pour les praticiens d'aujourd'hui que ne le laisse penser le droit consulaire moderne. Par exemple, lorsque le consul Annibale de Rossetti, en Égypte, dut trancher un litige entre deux commerçants allemands, il fut dépassé par la situation. De Rossetti ne connaissait ni l'allemand, ni le droit qu'il était censé appliquer. Les consuls modernes réagissent souvent avec incrédulité en apprenant que leurs prédécesseurs exerçaient à la fois les fonctions de juges, d'autorités réglementaires et d'huissiers de justice. De volume réunit des contributions portant sur l'histoire des rôles et fonctions juridiques des consulats, de l'Amérique à la Chine, depuis leurs origins au Moyen Âge jusqu'au consulat moderne.